(untitled) (London Journal of Research In Science: Natural and Formal, 2026)
Scanty information is available about importance of feeding of Tinospora cordifolia on the health and production of livestock. An investigation was conducted to study the effect of different levels of Tinospora cordifolia in HDK – 75 pigs. Twenty Four (24) number of pigs were randomly divided into four groups i.e. Control, T1, T2, and T3 groups containing six (6) animals in each group. The T1, T2, and T3 groups were the treatment groups where the stem of Tinospora cordifolia (Giloy) were dried and in powdered form were given @ the rate of 0.5 %, 1.0 % , 1.5 % respectively mixed with rations. . The experimental rations were prepared according to BIS 1994 during 180 days experimental period. Compared to control and T1 group, by supplementation of Tinospora cordifolia the average daily body weight gain was seen highest T3 group (P 0.05 ) has been seen between the treatment and control groups. Histopathological study and blood parameters shows that supplementation of Tinospora cordifolia does not have any negative effect on liver and kidney. But supplementation of Tinospora cordifolia shows positive changes in T3 group compared to control group.